British Humanitarian Political Economy and Famine in India, 1838–1842. (April 2020) - Major, Andrea
Abstract: This article explores the nature and limitations of humanitarian political economy by discussing metropolitan British responses to a major famine that took place in the Agra region of north-central India in 1837–38. This disaster played a significant role in catalyzing wider debates about the impact of East India Company governance and the place of the subcontinent within the post-emancipation British Empire. By comparing the responses of organization such as the Aborigines Protection Society and British India Society to that of proponents of the newly emergent indenture system, the paper seeks to contextualize responses to the famine in terms both of longer histories of famine in South Asia and of the specific imperial circumstances of the late 1830s. In doing so, it explores how ideas of agricultural distress in India fed into competing strategies to utilize Indian labor in the service of colonial commodity production both within India and around the empire.